PENINGKATAN MOTIVASI BELAJAR MATEMATIKA MELALUI STRATEGI PEMBELAJARAN THINK-TALK-WRITE (TTW) PADA SISWA KELAS V MI MUHAMMADIYAH NGASEM KECAMATAN COLOMADU TAHUN PELAJARAN 2013/2014 - Minsih Minsih; Dwi Astuti (Profesi Pendidikan Dasar, 2014)
This study aims to increase the motivation to learn mathematics through the learningstrategy Think-Talk-Write (TTW) fifth grade students of Muhammadiyah Ngasem MI.Subjects were teachers and students of class V. The object of research is learning motivationand learning strategies Think-Talk-Write (TTW). The research process was conductedin two cycles, each cycle consisting of two meetings. Each cycle consists of four stages,namely: planning, action, observation, and reflection. Data collection techniques usedthrough observation, tests, interviews and documentation. Instrument used in this study isthe observation sheet, guidance interviews, tests, assessment guidance document data.Data analysis technique used consists of three components, namely: data reduction, datadisplay, and conclusion. Test the validity of using triangulation and triangulation methods.Indicators of success is the achievement of 75% on each of the indicators. The resultsshowed an increase in motivation to learn mathematics. 1) the readiness of students tofollow the learning cycle I II 67.2% 80.4% cycle 2) activity of students in a discussion witha friend the first cycle II 65.2% 82.6% cycle 3) the ability of students working on the firstcycle 58.7% second cycle 84.8% 4) the courage to ask questions first cycle 50% cycle II79.2%. The conclusion of this research is the application of learning strategies Think-Talk-Write (TTW) can increase students’ motivation to learn mathematics class V MIMuhammadiyah Ngasem Colomadu District of Academic Year 2013/2014.